Analisis Metode Reading Guide Terhadap Keterampilan Membaca Bahasa Arab Siswa Kelas VII-C Bahrul Ulum Natar Lampung Selatan: Analisis Metode Reading Guide Terhadap Keterampilan Membaca Bahasa Arab Siswa Kelas VII-C Bahrul Ulum Natar Lampung Selatan - Dwi Aprilia Damayanti; Rima Ajeng Rahmawati; Muhammad Wisnu Khumaidi. (Program Studi Pendidikan Bahasa Arab, 2023)
The background of this research is based on the fact that there are still many students who think that Arabic is the most difficult subject and are not familiar with Arabic lessons because most of them are graduates from elementary school. The purpose of this study was to determine the effectiveness of the reading guide method on the Arabic reading skills of class VII-C students of MTs Bahrul Ulum. This research using descriptive-qualitative methods. The application of the method carried out in stages is quite good. The reading guide method is able to encourage students to improve the quality of their reading skills. There are several obstacles in the application of the reading guide method including the lack of students' understanding of the material there are : students chatting during the learning process, the lack of time allocation and there are still many students who are not fluent in reading Arabic texts. The teacher's efforts to minimize this problem are the teacher admonishing students who chat during the learning process by approaching students who chat, both teachers train students in reading Arabic texts by means of students repeating their readings. From these results it can be concluded that the use of the reading guide method in learning Arabic can accelerate teachers in completing learning material and train students in reading Arabic texts, but this method is still less effective when applied in seventh grade.